2020
DOI: 10.3390/ijms21155301
|View full text |Cite
|
Sign up to set email alerts
|

Translation Regulation by eIF2α Phosphorylation and mTORC1 Signaling Pathways in Non-Communicable Diseases (NCDs)

Abstract: Non-communicable diseases (NCDs) are medical conditions that, by definition, are non-infectious and non-transmissible among people. Much of current NCDs are generally due to genetic, behavioral, and metabolic risk factors that often include excessive alcohol consumption, smoking, obesity, and untreated elevated blood pressure, and share many common signal transduction pathways. Alterations in cell and physiological signaling and transcriptional control pathways have been well studied in several human NCDs, but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 219 publications
(311 reference statements)
2
19
0
Order By: Relevance
“…A survey report by the World Health Organization (WHO) pointed out that NCDs have become the primary factor of human death [ 2 ]. The main harm of NCDs is to cause damage to important organs such as heart, brain, and kidney, and lifelong diseases [ 3 ]. According to statistics, the incidence of NCDs such as diabetes, cardiovascular disease, chronic respiratory disease, and cancer has been increasing year by year in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…A survey report by the World Health Organization (WHO) pointed out that NCDs have become the primary factor of human death [ 2 ]. The main harm of NCDs is to cause damage to important organs such as heart, brain, and kidney, and lifelong diseases [ 3 ]. According to statistics, the incidence of NCDs such as diabetes, cardiovascular disease, chronic respiratory disease, and cancer has been increasing year by year in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…ERK/MAPK and PI3K/AKT/mTOR signalling responses play important roles in Middle East respiratory syndrome coronavirus (MERS-CoV) infection [ 24 ]. The key role in the synthesis of proteins essential for these mechanisms belongs to mTOR (mammalian target of rapamycin) complexes and signalling pathways involved in mTOR regulation including eIF2α [ 25 ]. mTOR is a serine/threonine protein kinase in the PI3K-related kinase (PIKK) family that forms the catalytic subunit of two distinct protein complexes, known as mTOR Complex 1 (mTORC1) and 2 (mTORC2).…”
Section: Introductionmentioning
confidence: 99%
“…The top 1 ingenuity canonical pathway was EIF2 signaling, and this (Figure 7D), together with the IPA on ribosome protein genes, further confirmed that EIF2 signaling was the key driver of the TNBC metastasis in human. To further confirm that, we checked the expression of the major component genes of EIF2 signaling and found upregulation of multiple genes, including EIF2AK1 (HRI protein coding gene), EIF2AK2 (PKR protein coding gene), EIF2AK4 (GCN2 protein coding gene), EIF2B5, and AKT2 (Figure 7E; Rios-Fuller et al, 2020). Other ingenuity canonical pathways included regulation of eIF4 and p70S6K signaling and mTOR signaling (Figure 7D), both of which were closely associated with TNBC biological activities (Madden et al, 2014;Wang et al, 2017;Zagorac et al, 2018).…”
Section: Activated Eif2 Signaling In Metastatic Tnbc Cellsmentioning
confidence: 84%